EXPERIENCES TO GO ON INTERNATIONAL EXPEDITIONS (Study of Phenomenology in Students Outdoor Club) - MUHAMAD RIDZKI HIDAYAT; Achmad Mujab Masykur (Jurnal EMPATI, 2017)
Popularity of outdoor activities has been increasing significantly in the past 15 to 20 years across the world. It has also became the fastest growing among any other sporting activities (Monasterio, Alamri dan Mei-Dan, 2014). Mahasiswa Pecinta Alam or shorten as Mapala (Indonesian term for college students who joined outdoor or adventure club) who are born in this nation, have desire to explore and brought up Indonesia’s name internationally through their adventure activities. The desire later manifested into a form of expedition. Expedition defined as a journey of scientific research and investigation particularly in less known areas. An expedition is hereby interesting to be researched since there are only a few literatures that discussed about this discourse. This research is using qualitative phenomenology approach. Furthermore in this research, interview and field notes or recording are being used for data collection procedures. All collected datas later analysed with DFI data explication technique which divided the experience to go on an international expedition in four episodes. The subjects in this research consist of three person approched by purposive technique. All of the three subjects are member of Mapala with three different type of international expeditions which are; kayaking (L, 21, Palapsi UGM), wall climbing (L, 23, Astacala Tel-U), and iceberg climbing (P, 19, Mapagama UGM). The overall result of this research shows how management and functionality of team are foremost important due to the success of an expedition. Aside of this aspect, the research also shows that tthere are changes within the subjects’ notably before the expedition until aterwards. The changes can be analysed with triadic reciprocal causation Bandura model